Qualified foreign institutional investors and corporate innovation: From the perspective of corporate governance - Wang, Xiao; Wang, Wanting; Shi, Xiang yan (Frontiers in Psychology, 2022)
Whether qualified foreign institutional investors can effectively play a governance role in the capital market and guide the transformation of corporate innovation from “high-volume and low-quality” to “high-volume and high-quality” is an important issue in the process of foreign capital introduction at the present stage. From the perspective of how QFII shareholding affects the innovation model of firms, this study analyzes the data of China’s A-share listed companies from 2007 to 2018 and finds that the shareholding of qualified foreign institutional investors has significantly improved the innovation level of the invested firms, which is reflected in the increase of innovation output and the improvement of innovation quality. The mediating effect shows that QFII shareholding can improve the innovation level of corporates by slowing down insider tunneling of holding companies and increasing the number of analysts to follow, which indicates that QFII is conducive to improving the governance structure of listed companies and improving their qualities. Further research finds that QFII shareholding has a positive impact on corporate efficiency by improving the level of corporate innovation. The above conclusions provide experience and reference for China to further introduce foreign capital.